A comparative study assessing sleep duration and associated factors among adolescents studying in different types of schools in an urban area of Kerala, India - Geethu Mathew; Aby Dany Varghese; Anoop Ivan Benjamin (Wolters Kluwer Medknow Publications, 2019)
Background: Sleep is essential for optimizing physical, cognitive, and emotional functioning of adolescents. Adolescents are one of the most sleep-deprived age groups in the society. Objectives: To assess sleep duration and associated factors among adolescent children studying in different types of schools in an urban area of Kerala. Methodology: This cross-sectional study was conducted in Pathanamthitta district, Kerala, from January to December 2017. All adolescent children studying in high school and higher secondary classes were included using stratified random sampling. Study tool included a questionnaire which collected sociodemographic information, sleep duration, and schedule. Results: In this study, 657 students were enrolled. The mean age of the participants was 15.09 ± 1.33 years. 201 students (30.6%) were from government school, 242 (36.8%) from aided, and 214 (32.6%) were from private school. The mean sleep duration among the students was 7.2 ± 1.26 h. Sleep duration was found to be inadequate in 60% of the children. The sleep duration was found to be longer during weekends compared to weekdays. Nearly 92% of students take a daytime nap of> 1 h during weekends. Private school students had inadequate sleep duration, late bedtime, and early wake-up time compared to other students. Higher age, class, education of parents, family income, distance travelled to school, and female gender were the other factors associated with inadequate sleep among adolescents. Conclusion: Inadequate sleep duration and difference in sleep schedule during weekends were observed among adolescents, especially among private school students. Primary prevention approach aimed at spreading adequate awareness regarding the importance of sleep among students, parents, and teachers should be practiced.